Superconducting-state properties and electronic band structure calculations of a noncentrosymmetric Th7Ni3 compound. (2nd November 2018) - Idczak, R; Sahakyan, M; Tran, V H
Abstract: Superconducting-state properties of a noncentrosymmetric Th7 Ni3 compound have been investigated using magnetic, electrical resistivity and specific heat measurements as well as by electronic band structure calculations. The study reveals that the studied compound is a dirty type-II superconductor with K and a weak electron–phonon coupling . Moreover, in contrast to an exotic superconductivity observed previously in Th7 Fe3 and Th7 Co3, data reported in this paper give clear evidence that Th7 Ni3 is a conventional single-gap superconductor. The experimental results are supported by DFT calculations of the electronic band structure, density of states, electron localization functions and Fermi surfaces which were performed using the full-potential linear muffin-tin-orbital and full-potential linearized augmented plane wave methods. Theoretical data show that asymmetric spin–orbit coupling in Th7 Ni3 is quite small; hence the electronic band structure of this compound is weakly affected by the spin–orbit effects. We have determined fundamental parameters of Th7 Ni3 and compared the superconducting properties with other Th7 T3 (T = Fe, Co and Ru) compounds.